Perspektif Al-Qur’an tentang Sel Saraf dalam Kajian Integrasi Agama dan Sains - Maulidya Hasanah; Alfina Wildatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Al-Qur'an is one of the sources of knowledge that has absolute truth. This source of knowledge does not only focus on knowledge about worship and muamalah, but also on scientific insights, namely scientific facts. These scientific cues are found in the verses of the Qur'an which are scattered throughout the surah and are referred to as kauniyah verses. One of the scientific signs explained in the Qur'an is about nerve cells. There are six verses spread across three suras in the Al-Qur'an with an indirect pattern of conveying information so that it requires further study to understand the meaning and scientific signals. The word